Helicobacter pylori infection diagnostics and choice of eradication treatment: results of inquiry of doctors from different regions of Russian Federation - N. N. Dekhnich; R. S. Kozlov; O. A. Sablin; Ye. A. Prischepova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate doctors’ awareness on diagnostic methods and eradication treatment modes of Helicobacter pylori (H. pylori) infection in routine clinical practice. Material and methods. Overall 261 doctors of healthcare institutions in 15 cities of Russia (Orel, St. Petersburg, Veliky Novgorod, Smolensk, Krasnoyarsk, Ulyanovsk, Krasnodar, Arkhangelsk, Yaroslavl, Ufa, Bryansk, Kaliningrad, Nizhny Novgorod, Moscow and Tyumen) were surveyed in 2016-2017. Data acquisition provided voluntary anonymous application of questionnaire consisting of 12 questions that will allow estimating knowledge of indications to H. pylori testing, diagnostic methods for this infection and utilized antihelicobacter treatment modes. Results. Primary diagnostics of H. pylori infection is carried out at peptic ulcer and chronic gastritis by 85 and 84% of surveyed doctors, at GERD - by 59.4%, at NSAID -related gastropathy - by 32%, at MALT lymphoma by 32%, at stomach cancer - by 30.7% and at autoimmune thrombocytopenia - by 16.8% respectively. Primary diagnostics of infection is based mainly on invasive methods: histological method (41.8% of respondents) and rapid urease test (38%). Noninvasive diagnostic methods for H. pylori infection: 13C urea breath test, stool test for H. pylori antigens and serological method were applied by 29.5%; 32.2% and 34.4% of respondents respectively. Of 241 described antihelicobacter first-line treatment modes 49.8% of respondents checked completely adequate treatment in accordance to the Russian Gastroenterological Association (RGA) guidelines. Of specified modes mainly clarithromycinbased standard triple therapy, including combination to the bismuth agent was mentioned. H. pylori eradication efficacy control is carried out by adequate invasive tests, such as urea breath test and fecal antigen test being utilized by 17.4 and 16.2% of respondents respectively. The inadequate control using serological method and rapid urease test was recommended by 10.7 and 6.6% of surveyed doctors respectively. At the choice of second line antihelicobacter therapy mode components 34.8% of doctors complied to RGA guidelines. Quadrotherapy with bismuth agent was advocated by 28% of doctors, levofloxacin-based triple therapy by 6.8%. Conclusions. Overall, doctors from different regions of the Russian Federation are well aware of the primary diagnostic methods of H. pylori infection, indications for eradication therapy and first-line treatment mode. However, additional education is required to inform doctors on necessity for H. pylori eradication, efficacy control methods, mode of second line treatment and drug dosages.